Prenatal diagnosis of chromothripsis causing complex chromosomal rearrangement involving chromosomes 5, 7 and 11 leading to TWIST1 deletion and Saethre-Chotzen syndrome - Ivana Joksic; Mina Toljic; Nela Maksimovic; Dijana Perovic; Tatjana Damnjanovic; Aleksandar Jurisic (Taiwanese Journal of Obstetrics & Gynecology)
Objective: Prenatal detection of complex chromosomal rearrangements (CCR) is extremely rare, but is of great clinical importance, since CCR can be causative of different congenital disorders. We present an exceptionally rare case of prenatally diagnosed Saethre-Chotzen syndrome (SCS) rising as a consequence of chromothripsis involving chromosomes 5, 7 and 11 and deletion of TWIST1 gene. Case report: Brachycephaly, hypertelorism, flat face, micrognathia, relative macroglossia and small posterior fossa were noted on ultrasound examination at 28th gestational week. Fetal karyotyping revealed de novo translocation 46,XY,t(7;11)(p15.5;q21)dn. Chromosomal microarray showed presence of three microdeletions on chromosome 7 (7p21.1p15.3 including TWIST1, 7p12.1p11.2 and 7q21.11), and one on chromosome 5p12p11. Conclusion: Use of advanced molecular diagnostic techniques in combination with cytogenetic methods allows for precise characterization of CCRs and detection of molecular mechanisms of their origin. Phenomenon of chromothripsis can be causative of rare genetic syndromes such as SCS.